If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2y + -2y) + -1y = -3(y + -3) Combine like terms: 2y + -2y = 0 -3(0) + -1y = -3(y + -3) Multiply -3 * 0 0 + -1y = -3(y + -3) Anything times zero is zero. 0 + -1y = -3(y + -3) Remove the zero: -1y = -3(y + -3) Reorder the terms: -1y = -3(-3 + y) -1y = (-3 * -3 + y * -3) -1y = (9 + -3y) Solving -1y = 9 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. -1y + 3y = 9 + -3y + 3y Combine like terms: -1y + 3y = 2y 2y = 9 + -3y + 3y Combine like terms: -3y + 3y = 0 2y = 9 + 0 2y = 9 Divide each side by '2'. y = 4.5 Simplifying y = 4.5
| 0.6(10n-3)=-1.5(n+2)-0.3 | | (v+10)12= | | -(5a+6)=-4(-f+2) | | 2x+2=161 | | -8x+1=81+2k | | h(t)=-16t^2+64+9 | | 6a+25=8a+3 | | 183.6+-109.3=x | | 6y^2+12=6y | | 12b-38=b+28 | | 5x+2x=13x-2x+16 | | 85=-7x-4x+8 | | 6(6-7)7=56 | | 9s+42=s+50 | | 5x-9+10=31 | | t=3t-38 | | 8x=.5(3x+2) | | 34+8m=17m+7 | | -10-5x-7x=110 | | 10n+5n=50 | | 10=-16x^2+96x | | (x-2)(x-6)=2x-(b+2)x+2b | | 3x+23=35 | | 2x-8x+6=x-9+15 | | 3c-8=32 | | 3c-8=32 | | 11=18+7 | | 2t^2+9=0 | | 11x+5+(8x-15)=180 | | x+10+x=-2-x | | 4x+3=5x+2 | | -9-8x=-9x+16 |